Karl Polanyi on Strategy: The Effects of Culture, Morality and Double-Movements on Embedded Strategy - Faulconbridge, James; Muzio, Daniel (Social Science Research Network, 2019)
Karl Polanyi is arguably one of the most significant economic sociologists. At first glance the links between Polanyi’s ideas about markets, society and institutions and strategy may not be obvious. However, there is a hereto unrecognised link between recent writing about institutions and strategy and Polanyi’s work. In this paper we, therefore, chart how, when recognised, these links reveal that Karl Polanyi’s work might provide new ways of thinking about strategy. Our over-riding claim is that Polanyi’s ideas reveal the importance of considering how strategies are defined, responded to, and ultimately rendered effective or ineffective in ways that are determined by relationships between markets, the state and society. It is thus crucial to understand strategy as embedded, this implying consideration of a strategy’s legitimacy in economy and society as an instituted process at any particular place and time. This also implies wider political questions about strategy in society and the extent to which strategists need to be aware of the ‘double movement’ Polanyi discusses and ensure strategies serve the interests of society as well as those of the market. KM: from forthcoming book "Critical perspectives on Accounting"
Keywords: double movement; embeddedness; professional services; strategy

Karl Polanyi and economics: Polanyi's pendulum in economic science - Kretschmer, Mark (Ordnungspolitische Diskurse, 2019)
Since the crisis of 2008 the liberal market order has been challenged by several (populist) social movements and has become object of political regulation. Whereas in the late 70s and early 80s politics tend to deregulate the market, nowadays deregulation seem to be a synonym for the negative externalities of a free global market. Following Polanyi (The Great Transformation, 1944), societies with market market economies tend to experience a double movement - the Polanyi's Pendulum - between phases in which the policies are designed to restrict the markets or liberalize them. This paper raises the question if these indicated changes have an impact on the economic research topics. Referring to modern Varieties-of-Capitalism literature bibliometric data of the period between 1950 and 2015 are used to analyze if there is a Polanyi's Pendulum within the economic literature. Looking for specific key words, e.g. liberalization, and using correlation analyses and time-series regressions it is possible to determine changes of the topics economists worked on and to identify those economic macro-forces that have been driven these changes. The political development in recent years can be considered as a new swing of Polanyi's pendulum. Economics itself is part of the double movement. A second look at Polanyi's might be fruitful to face present challenges better equipped.
Keywords: Polanyi's pendulum; bibliometry; double movement; political economy; varieties of capitalism

Proprietary Law Schools and the Marketization of Access to Justice - Tejani, Riaz (Social Science Research Network, 2016)
The rise of for-profit law schools in the United States highlights the interplay of political and moral economy in the reproduction of legal expertise. This article offers ethnographic evidence from one ABA-accredited for-profit law school pseudonymously labeled New Delta School of Law. The article posits New Delta as a case study in market fundamentalism of the kind first theorized by Hungarian economist Karl Polanyi. Polanyi defined global capital as a “double movement” between free marketeerism on the one hand and countervailing social protectionism on the other. Treating this as incomplete, social philosopher Nancy Fraser has since argued that the emancipatory new social movements form a third element in what should more properly be considered a “triple movement.” In this article, I argue that for-profit law schools such as New Delta support Fraser’s revision. Drawing in capital commitments from large institutional investors with promises of high returns on the basis of guaranteed federal student loan dollars, New Delta recruits disproportionately from minority and low-income communities while offering low chances of bar passage and legal employment. By marrying free marketeerism with the discourse of emancipation, the school has successfully evaded scrutiny.
Keywords: anthropology; economic; finance; law; legal education; markets; morals; neoliberalism; race; regulation; triple movement

Markets and Society - Zaman, Asad (Social Science Research Network, 2015)
In face of the strong conflict between market norms and social norms, peaceful co-existence is impossible. In traditional societies, markets were subordinated to society. Modern society emerged via a number of revolutions which made society subordinate to markets. This led to a reversal of traditional values of social cooperation and harmony with nature. Instead, men, nature, society became objects to be exploited for creating profits. A market society generates profits by exploiting men and nature, and requires increasing profits to sustain itself. This process has run into its limits as planetary resources are being destroyed on a scale large enough to threaten the planet. Saving the planet requires reversing the transition to modernity by subordinating markets to society. This is a difficult task.
Keywords: Great Transformation, The (Book); environmental economics; exploitation; market society

A Crisis of Executive Managerialism in the EU: No Alternative? - Joerges, Christian; Weimer, Maria (Maastricht Faculty of Law Working Paper No. 2012-7, 2012)
Against a backdrop of rapidly evolving crisis management in the European financial and sovereign debt crisis this essay aims both to explore and to re-consider the role of law in the EU integration process: What did law accomplish? Where did it fail? What is law going to endure? What kind of future can it envisage? The essay traces back the evolution of the law-politics relationship in both EU legal scholarship and practice from the foundational period of ‘integration-through-law’ to the advent of ‘new governance’ in the EU, and finally to the current deep transformations of EU law in new economic governance and the financial crisis. The centrality of law as ‘both the object and the agent’ of European integration, and the legal enshrinement of EU’s economic constitution has recently neglected the weight of ‘the social’ in the societies of post-war Europe, a failure which was to become detrimental to both domestic social stability and the legitimacy of integration. Attempts to cure Europe’s social deficit by re-conceptualizing the notion of law as new governance have widened the theoretical perspective of EU legal scholarship. Yet new governance has not delivered more social democracy and justice in Europe in practical terms, and continues to suffer from the methodological problems of its ‘definition-by-contrast.’ These problems re-emerge in current new economic governance, which Europe’s crisis management is generating. This hybrid arrangement of hard and soft law instruments has, to date, been economically unsuccessful and socially disastrous, especially in the South of Europe. Equally disquieting, the notion of democratic law (either in traditional or experimentalist understandings) has been replaced by a praxis of authoritarian executive managerialism. The essay concludes by sketching out an alternative understanding of law-mediated legitimacy in the integration process, namely ‘conflicts-law constitutionalism’. This approach stresses the normative value of conflicts and pluralism in the process of European integration. Instead of ‘ever more Europe’ it aims to secure the existing democratic credentials of EU law, namely its ability to correct the democratic deficit of the Member States while respecting their constitutional integrity.
Keywords: EU economic constitution; EU financial crisis; European Union; governance; unity in diversity

Polanyi's Embeddedness and Shareholder Stewardship: A Contextual Analysis of Current Anglo-American Perspectives on Corporate Governance - Talbot, Lorraine E. (Social Science Research Network, 2012)
Polanyi saw the economy as properly embedded in society and argued that the capitalist free market, in commodifying social relations of production, seeks to disembed the economy from society. The resulting lack of continuity between society and economy, he maintained, created conflict which necessarily required state intervention. The market economy, therefore, in contrast to neoclassical/neoliberal economics’ vision of an autonomous, self-regulating market, required more, not less, state intervention to sustain it than alternative, more embedded economies. This article explores this conflict in the context of a specific neoliberal claim: that institutional shareholders are capable of being good “stewards” of the companies in which they invest. Utilising Polanyi’s embeddedness, this article assesses the “stewardship” approach as it is manifested in the US and in the UK. This approach is posited on a vision of a disembedded, self-regulating market. Putting it into practice is thus a retrograde step which will only exacerbate the problems created by the market-based corporate governance strategies which have prevailed since the late 1970s onwards.
Keywords: Polanyi; conflict; crisis; embeddedness; shareholder stewardship

Karl Polanyi and the New Economic Sociology: Notes on the Concept of (Dis)Embeddedness - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2011)
Within the context of the New Economic Sociology, Karl Polanyi is almost universally considered the "father" of the concept of embeddedness. However, this concept has been subject to selective appropriation by this discipline and its relationship to the remaining theoretical edifice constructed by Polanyi has been neglected. It is, in fact, possible to refer to the "great transformation" to which the concept of embeddedness has been subjected: whereas in Polanyi’s work it is associated with the macro(economic) level and is used as evidence of the exceptional nature of the capitalist market economy –- disembedded from society –- in NES, it is normally associated with the meso (and even micro) level, on the assumption that all economies –- including capitalist economies -– are embedded. in RCCS Annual Review, No. 3, pp. 119-140
Keywords: Karl Polanyi; capitalism; embeddedness; market economy; new economic sociology

The Idea of a Three-Dimensional Conflicts Law as Constitutional Form - Joerges, Christian (RECON Online Working Paper 2010/05, 2010)
‘Constitutionalisation’ is the key concept in the search for legitimate governance in the European Union and in the international system. This paper suggests the revitalising of a discipline which is widely neglected in European law and international law scholarship. It does not, however, recommend a return to the conflict of laws (private international law) in the traditional sense. The new type of conflicts law that the paper advocates is not concerned with selecting the proper legal system in cases with connections to various jurisdictions. This conflicts law is conceptualised as a response to the increasing inter-dependence of formerly more autonomous legal orders and to the democracy failure of constitutional states which result from the external effects of their laws and legal decisions on foreign systems and on their citizens who cannot understand themselves as their authors. European law has a vocation and many means both to compensate for the democracy failures of member states and to build upon this potential in its constitutionalisation. The conflicts law approach also provides new, albeit more restrained, perspectives at international level. WTO law is used to explore and document its constitutional perspectives. The conflicts law approach is differentiated into three dimensions. With this differentiated fabric, the approach responds to transformation processes which have affected contemporary law at all levels of governance after the rise of regulatory politics and the turn to governance. In its second dimension, conflicts law seeks to constitutionalise co-operative problem-solving under the lead of administrative bodies, while its third dimensions is concerned with both the recognition and the supervision of transnational governance arrangements and para-legal regimes.
Keywords: BLOCK, Fred; Europeanisation; World Trade Organization (WTO); always socially embedded' economy; constitutionalisation; deliberative democracy; economic law; economic sociology; multilevel governance; private international law; rule of law; social embeddedness; social regulation; supranationalism

Polanyi in Brussels? Embeddedness and the Three Dimensions of European Economic Integration - Höpner, Martin; Schäfer, Armin (Max-Planck-Institut für Gesellschaftsforschung, 2010)
In a recent article, Caporaso and Tarrow have argued that the jurisprudence of the European Court of Justice (ECJ) is increasingly moving in a social policy direction that will ultimately put European politics on a “Polanyian” course. We take issue with their claim and distinguish three dimensions of European economic and social integration: market-correcting integration, market-enforcing integration, and the creation of a European area of nondiscrimination, the latter consisting of two subdimensions, namely nondiscrimination on the basis of characteristics such as gender, age, and ethnic origin, on the one hand, and nondiscriminatory transnational access to the social security systems of the member states, on the other. Increased heterogeneity among European varieties of capitalism perpetuates the different ranges and speeds of these integration dimensions. We conclude that the Polanyi-in-Brussels hypothesis is misleading. Politically enforced social integration has not made much progress in the last decades, while market-enforcing integration and European nondiscrimination policies have asymmetrically profited from “integration through law.” So far, the impact of European integration on political economy has been “Hayekian” rather than “Polanyian.” Jüngst haben Caporaso und Tarrow argumentiert, die Rechtsprechung des Europäischen Gerichtshofs (EuGH) weise zunehmend soziale Züge auf und führe dazu, dass die europäische Integration eine „Polanyische“ Richtung einnehme. Wir wenden uns gegen diese These und unterscheiden drei Dimensionen der europäischen Wirtschafts- und Sozialintegration: die marktkorrigierende Integration, die marktschaffende Integration und die Schaffung eines europäischen Antidiskriminierungsraums, wobei letztere aus zwei Subdimensionen besteht, nämlich der Nichtdiskriminierung aus Gründen wie denen des Alters, der ethnischen Zugehörigkeit und des Geschlechts einerseits, und der Durchsetzung eines diskriminierungsfreien transnationalen Zugangs zu den sozialen Sicherungssystemen der Mitgliedstaaten andererseits. Die gestiegene Heterogenität europäischer Spielarten des Kapitalismus perpetuiert die unterschiedlichen Reichweiten und Geschwindigkeiten der Integration in den drei Dimensionen. Wir kommen zu dem Ergebnis, dass die „Polanyi in Brüssel“-These unzutreffend ist. Während die politisch herbeigeführte, soziale Integration kaum Fortschritte macht, profitieren die marktschaffende Integration und die europäische Antidiskriminierungspolitik von der „Integration durch Recht“. Die europäische Integration trägt daher weit mehr „Hayeksche“ als „Polanyische“ Züge.
Keywords: Europe; Polanyi-in-Brussels hypothesis

Polanyi and the Instituted Processes of Markets: Introducing a Wellbeing Perspective - Johnson, Susan (2009)
Analysis of the role of markets in development is mainly focused on their ability to promote material provisioning. Polanyi argued that markets were only one approach to material provisioning, and that the concept of the self-regulating market had become disembedded from society. He was concerned that processes of provisioning be understood within the wider framework of society and developed the concept of instituted process as a means to understand this role. This paper sets out to explore whether and how Polanyi’s concept of instituted process might work with emerging approaches to analysing wellbeing – what it means to live well – to offer tools for the institutional analysis of markets.
Keywords: embeddedness; instituted economic process; instituted process; institutions; well-being

The Great Transition - Spratt, Stephen; Simms, Andrew; Neitzert, Eva; Collins, Josh-Ryan (New Economics Foundation, 2009)
Maps out a set of solutions to various systemic problems "This report argues that nothing short of a Great Transition to a new economy is necessary and desirable, and also possible. " - We have called the process by which this could happen the Great Transition as a deliberate echo of The Great Transformation, written by Karl Polanyi in the 1940s.1 While in a relatively short report such as this we could not hope to achieve anything remotely comparable to Polanyi’s great work, the scale of the change we need to see is at least the equal of the changes he described. Polanyi analysed how market processes in the industrial revolution had created severe ruptures in the fabric of social life, and argued strongly that we needed to reverse this and nd a balance between the market and the non-market; the private and the public; the individual and the community. We couldn’t agree more, and the need to achieve this is all the more pressing now given the huge environmental problems we face, problems that Polanyi could not have foreseen in 1944 when the world was caught in the bloody conclusions of the Second World War. The most pressing problem facing humanity now is how to share scarce planetary resources in ways that are just, sustainable and support the well-being of us all.
Keywords: environemntal politics; environmental value; redistribution

Conflict of Laws as Constitutional Form: Reflections on International Trade Law and the Biotech Panel Report - Joerges, Christian (Social Science Research Network, 2007)
Hardly anywhere is the trend towards a perfection of transnational governance arrangements and their “legalization” more visible than in international trade. Governance arrangements established through and alongside WTO law are both practically important and theoretically challenging. They do not just organise international trade relations. They also affect national and regional (European) regulatory policies partly directly, partly more indirectly. How can we explain and how should we evaluate their emergence? The WTO system of 1994, which replaced the GATT of 1947, responded to the ever increasing importance of non-tariff barriers to trade. These barriers reflect regulatory concerns especially in the fields of health and safety, consumer and environmental protection. There importance for WTO member is such that they cannot simply be abandoned for the sake of free trade. This is why the responses the new international trade system institutionalised by special agreements concerning on-tariff barriers to free trade such as the Agreement on the Application of Sanitary and Phytosanitary Measures (SPS) and the Agreement on Technical Barriers to Trade (TBT) reflect a politicisation of international trade. Can we conclude that international markets have been re-regulated and that international trade law ensures their “social embeddedness”? The paper seeks yardsticks for an answer to these questions in the debates on transnational constitutionalism. It submits that constutionalisation can and should be based on a conflict-of approach. For its elaboration of this suggestion, the paper first contrasts the jurdification of transnational governance at the European and the international level. It then discusses the WTO panel report on the Biotech dispute. It concludes that the legalisation and judicialisation in that case have remained “thin.” What can be observed is a political rather than a social and legal embeddedness of markets.
Keywords: FOUCAULT, Michel, 1926-1984; Polanyi and Foucault; World Trade Organization (WTO); constitutionalisation; economic law; embeddedness; european governance; international trade; legal embeddedness; legalization; legitimacy; multilevel governance; national autonomy; risk regulation; social embeddedness; transnational governance

Tanzanite: Commodity Fiction or Commodity Nightmare? - Donahue, Katherine Curtis (Social Science Research Network, 2007)
Karl Polanyi's discussion of the commodification of land, labour, and money is useful in analysis not only of nineteenth century markets but also of twenty-first century social and economic developments. This working paper explores the process of commodification of tanzanite, a gemstone discovered in the 1960s south of Mt. Kilimanjaro, Tanzania, and actively mined only since the 1980s. More rare than diamonds because the source area is limited to the Mererani hills east of Arusha, the gemstones reach markets through Maasai middlemen, foreign buyers, processors, cutters, polishers and dealers in Tanzania, India, Hong Kong, and the United States. The U.S. is responsible for 80% of the market for tanzanite. Production of the stone is occasionally slowed by flooding, accidents, and conflict over rights to mining areas. Children and teenagers often work in the tanzanite mines. These miners suffer death and disease not only because of unsafe mine conditions but also because of drug use and HIV/AIDS. Furthermore, this new commodity received close scrutiny after the attacks of September 11, 2001, because of a Wall Street Journal report that members of al Qaeda bought tanzanite for use in funding its networks and activities. This paper explores policy issues raised not only by that report and by global NGOs such as Global Witness, but also by the Tanzanian state, by health and safety workers and the miners and mining companies at Mererani. The paper is based on field interviews with buyers and sellers, in Tanzania and in the United States, as well as analysis of media reports, in order to argue that this particular commodity is, in Polanyi's terms, a fiction, one which has serious policy, social, health, and economic implications.
Keywords: Tanzania; Tanzanite; fictitious commodities; mining

The Great Transformation of Embeddedness: Karl Polanyi and the New Economic Sociology - Beckert, Jens (Social Science Research Network, 2007)
I argue that in its adaptation from Karl Polanyi’s The Great Transformation, the concept of embeddedness has itself undergone a great transformation. In the process, significant meanings of the concept have vanished, while others have been added. First I explore the different meanings the concept of embeddedness has achieved in the new economic sociology. Then I argue that it is not the embeddedness of economic action that should constitute the vantage point of economic sociology, but rather three coordination problems that actors face in economic exchange: the valuation of goods, competition and the problem of cooperation deriving from the social risks of exchange. I show that by proceeding from these coordination problems economic sociology, economic anthropology and economic history can find common research questions which allow them to enter into dialogue with each other more systematically. In the next section I focus on the social-reformist inclinations of Polanyi’s use of the notion of embeddedness and thereby highlight a challenge posed in The Great Transformation that was largely not taken up by economic sociologists. Finally, I discuss limitations for developing a macro theory of the economy that result from making embeddedness the core concept of economic sociology.
Keywords: economic history; economic sociology; embeddedness; political economy

Karl Polanyi - Isaac, Barry L. (Edward Elgar Publishing, 2005)
This unique Handbook contains substantial and invaluable summary discussions of work on economic processes and issues, and on the relationship between economic and non-economic areas of life. Furthermore it describes conceptual orientations that are important among economic anthropologists, and presents summaries of key issues in the anthropological study of economic life in different regions of the world. Its scope and accessibility make it useful both to those who are interested in a particular topic and to those who want to see the breadth and fruitfulness of an anthropological study of economics.
Keywords: economic anthropology; economics and finance; social policy and sociology

What We Need to Know About the Social Economy A Guide for Policy Research - PRI Project (Government of Canada, 2005)
This guide provides background on the social economy, identifies research issues whose examination would support the development of policies and programs, provides suggestions for how this research might be conducted, and points to some useful information sources. KM: Gov't commissioned - New Approaches for Addressing Poverty and Exclusion
Keywords: Canada; borderline; government of canada; grey literature; social economy

'Social Market Economy' as Europe's Social Model? - Joerges, Christian; Roedl, Florian (Social Science Research Network, 2004)
Europe continues to search for its - "European" - social model and the search seems to become increasingly urgent. It is no longer just the "democratic deficit", but also and alongside it, the "social deficit" of the EU which needs to be cured. That new concern is, in fact, a rejection of the older answers. According to the ordo-liberal interpretation of the European legal order as an "Economic Constitution" and, successively, in the analyses of the EU as a "Regulatory State", the sphere of social policy was to remain a domain of the nation state. This seems to have become impossible. The Constitutional Treaty, indeed, makes a new commitment: "The Union shall work for a Social Market Economy". This paper submits that this commitment is conceptually a failure, and politically not credible. The Convention preparing the Constitutional Treaty has apparently ignored the meaning of the concept in the form in which it was shaped in Germany's post-war period. This history entails some pitfalls for the Convention's intentions, as the German "Social Market Economy" involved not only a claim of integrating social concerns into the market economy, but also served to restrict claims for instruments of social policy remarkably at the same time. Moreover, the Convention has failed to confer a new and independent content to the concept of the "Social Market Economy", which could help to overcome the concept's ambivalent history, as well as the Union's real "social deficit". The few innovations, the Charter's Fundamental Social Rights and the Open Method of Co-ordination, were incorporated in such modest and non-committal forms that their potential to further the case for "social Europe" seems marginal. The paper concludes that the invocation of the "Social Market Economy" in the Constitutional Treaty is conceptually flawed and is politically an all too risky promise which may raise expectations which it will subsequently fail to deliver.
Keywords: constitution building; economic law; economic policy; governance; social deficit; social market economy; social policy

Politics, the state and the impulse for social protection : the implications of Karl Polanyi's ideas for understanding development and crisis - Putzel, James (London School of Economics Crisis States Research Centre working papers series 1, 18., 2002)
This short paper discusses how some of Karl Polanyi's key ideas can help shed light on the processes of development and crisis in the world today. It begins by taking up the role of economic liberalisation and the state. Then it discusses Polanyi's identification of the 'impulse' for 'social protection' and suggests it is crucial to an understanding not only of the role of the state in development but also politics in the developing world. It finishes by applying some of these ideas to understanding the actions of 11th September, and the crisis related to terrorism in the developing world today.
Keywords: development; economic theory; political institutions; social history; social problems; social protection; social reform

Polanyi, Market Fundamentalism, and the Institutional Structure of Capitalism - Burlamaqui, Leonardo (CEBRI Brazilian Center for International Relations, 2022)
The basic proposition of this paper is that the so-called "new economic sociology", which is rooted in key ideas of Karl Polanyi, is an indispensable "tool" for two tasks: a) it provides us with a powerful critique of market fundamentalism, and b) it allows us to analyze the economic performance of contemporary capitalism by accessing the working of its institutional structure. From an analytical perspective, the paper suggests that Polanyian Economic Sociology is an essential complement to both the Schumpeterian and the Post-Keynesian perspectives in economics. This is especially so when it comes to the discussion of "socioeconomic stability" and, more precisely, as Keynes himself stated in the General Theory: to explain why capitalist economies manifest themselves in different ways and degrees, in spite of encompassing inherent elements of instability and unpredictability.The basic proposition of this paper is that the so-called "new economic sociology", which is rooted in key ideas of Karl Polanyi, is an indispensable "tool" for two tasks: a) it provides us with a powerful critique of market fundamentalism, and b) it allows us to analyze the economic performance of contemporary capitalism by accessing the working of its institutional structure. From an analytical perspective, the paper suggests that Polanyian Economic Sociology is an essential complement to both the Schumpeterian and the Post-Keynesian perspectives in economics. This is especially so when it comes to the discussion of "socioeconomic stability" and, more precisely, as Keynes himself stated in the General Theory: to explain why capitalist economies manifest themselves in different ways and degrees, in spite of encompassing inherent elements of instability and unpredictability.
Keywords: Brazil; new economic sociology; political economy

Competition in transitional processes: Polanyi & Schumpeter - Hager, Theresa; Heck, Ines; Rath, Johanna (ICAE Working Paper Series, 2021)
We examine parallels and differences in the analyses of societal transition by Karl Polanyi and Joseph A. Schumpeter. We argue that although their understanding of historical processes differs - transformational-political vs. evolutionary-natural - the central mechanism of change they describe is the same. We identify three spheres essential to both authors' works: the economic, the political and the socio-cultural sphere. Polanyi and Schumpeter describe an expansion of the economic sphere culminating in a subordination of the other parts of society. In capitalism this dominance stems from capitalism's emergence as well as the concept of competition. The consequence is a profound change in societal relations. Changes in the socio-cultural sphere in turn produce changes in the political sphere that bring about detrimental consequences for democracy. In our paper we carve out the similarities as well as the differences in the respective theories, clarify the role competition plays therein and discuss the consequences for the political process. We adopt an analytical framework that puts the nearly analogous mechanism of change in the centre. This in turn enables us to make use of the complementarity and to gain valuable insights on the interdependence of capitalism and democracy that can inform trends and phenomena that are currently observed.
Keywords: SCHUMPETER, Joseph Alois, 1883-1950; competition; interdependence

The surplus approach, Polanyi and institutions in economic anthropology and archaeology - Cesaratto, Sergio; Bucchianico, Stefano Di (Department of Economics University of Siena, 2020)
This paper was inspired long ago by Jared Diamond (1997), and in particular by his extensive use of the concept of economic surplus as the key to the development of civilization. Unfortunately, Diamond does not mention the origin of the concept in classical and pre-classical economics, nor does he pay much attention to debates in economic anthropology about the role of economic analysis in studying primitive and ancient economic formations. These debates were the subject of a recent book by Cedrini & Marchionatti (2017), who dispute the neoclassical “imperialist” attempt to occupy the territory of economic anthropology. The authors rely on the institutionalist background provided by Karl Polanyi and his school and by other anthropologists of similar inspiration. Polanyians, however, fail to complete their institutional analysis by anchoring it to the changing modes of generation and distribution of the economic surplus. Yet their emphasis on the need to introduce institutions from the beginning, when speaking of economic surplus, should be taken into consideration by the classical surplus approach
Keywords: Marx; Polanyi; Sraffa; economic anthropology; economic archaeology; surplus approach